1998
DOI: 10.1002/(sici)1097-4547(19980915)53:6<697::aid-jnr8>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal astrocyte development and neuronal death in mice lacking the epidermal growth factor receptor

Abstract: Stimulation of the epidermal growth factor receptor (EGF-R) produces numerous effects on central nervous system (CNS) cells in vitro including neuronal survival and differentiation, astrocyte proliferation and the proliferation of multipotent progenitors. However, the in vivo role of EGF-R is less well understood. In the present study, we demonstrate that EGF-R null mice generated on a 129Sv/J Swiss Black background undergo focal but massive degeneration the olfactory bulb, piriform cortex, neocortex, and thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, severely abnormal placental development and immaturity of the lung were observed in Egfr-knockout mice, leading to spontaneous embryonic or perinatal death. Impaired neural development with progressive neurodegeneration resulting from elevated apoptosis of neural cells in the brain was also observed in these mice (129,145,203). These genetic studies demonstrate that Egfr is indispensable during development.…”
Section: A Physiological Signaling Of the Erbb Familymentioning
confidence: 81%
“…For example, severely abnormal placental development and immaturity of the lung were observed in Egfr-knockout mice, leading to spontaneous embryonic or perinatal death. Impaired neural development with progressive neurodegeneration resulting from elevated apoptosis of neural cells in the brain was also observed in these mice (129,145,203). These genetic studies demonstrate that Egfr is indispensable during development.…”
Section: A Physiological Signaling Of the Erbb Familymentioning
confidence: 81%
“…Mice surviving the first postnatal week are growth retarded and show abnormalities in skin 12, 14, 15, bone 16, 17, intestine 12 and brain 13, 15, 18 development, proving an essential role for EGFR signaling in multiple organs. Most EGFR knock‐out mice die before weaning age, although in very rare cases the mice can survive up to 1 month 12, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Most EGFR knock‐out mice die before weaning age, although in very rare cases the mice can survive up to 1 month 12, 14. Embryonic brain development proceeds inconspicuously in EGFR knock‐out mice, but postnatally a massive degeneration of the cerebral cortex and the olfactory bulbs can be observed, which is characterized by apoptotic death of neurons as well as astrocytes 13, 18. Degenerative processes can also be detected in the thalamus but thalamic astrocytes do not seem to be affected by apoptosis and can actively respond to the neuronal degeneration by inducing reactive gliosis.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the expression of growth factor receptors subsequently result in the specification of astroglial cells (see also Table 1). Here, it has been shown that the expression of the epidermal growth factor (EGF)-Receptor seems to be necessary for normal astrocyte development (Kornblum et al, 1998). While initial PDGF and FGF2 signals form these cells the cells themselves turn to a PDGF-R negative precursor cell (see also Figure 1).…”
Section: Introductionmentioning
confidence: 99%